"Śliczna gwiazda miasta Lwowa, Maryja" w malarsko-literackiej wizji Stanisława Wyspiańskiego (o projekcie witraża "Śluby Jana Kazimierza" i scenie historycznej "Królowa Polskiej Korony")= "The dazzling star of the city of Lvov, Maria" in the literary and artistic vision of Stanisław Wyspiański - Januszewicz, Maria (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article analyses the stained-glass window "The Vows of Jan Kazitnierz" by Stanisław Wyspiański and the historical scene "The Queen of the Crown of Poland".
Keywords: Wyspiański, Stanisław (1869-1907)